Anthropological Context of Professional Teacher Training (Journal of Advanced Research in Social Sciences, 2019)
A typological profile of students mastering the teaching profession has been developed based on the results of the empirical research carried out by universities of Belarus that provide professional teacher training programs. About 24% of students are classified as “undecided”. This type is characterized by a lack of orientation towards the teaching profession and dissatisfaction with the educational process at university. We assumed that the creation of an educational environment focused on the development of an individual style of professional activity and coordination of individual and generalized educational pathways of students at all stages of their professionalization in high school can change the situation. Such an educational environment can manifest itself in a multi-style educational space that meets the needs of students in professionalization in the context of individual educational requirements and generates factors of effective development and self-development of learners. Testing of the model of the multi-style educational space proved that it expands the possibilities of creative self-realization of future teachers, the achievement of the high level of educational standards, and significantly reduces the percentage of graduates who are not satisfied with the educational process at the university.